2012
DOI: 10.1038/nature10913
|View full text |Cite
|
Sign up to set email alerts
|

A new understanding of the decoding principle on the ribosome

Abstract: During protein synthesis, the ribosome accurately selects transfer RNAs (tRNAs) in accordance with the messenger RNA (mRNA) triplet in the decoding centre. tRNA selection is initiated by elongation factor Tu, which delivers tRNA to the aminoacyl tRNA-binding site (A site) and hydrolyses GTP upon establishing codon-anticodon interactions in the decoding centre. At the following proofreading step the ribosome re-examines the tRNA and rejects it if it does not match the A codon. It was suggested that universally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
457
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(511 citation statements)
references
References 30 publications
40
457
2
3
Order By: Relevance
“…We identify two features of translation systems that are relevant. First of all, in the decoding center of the ribosome, proofreading of anticodon base pair attachments to mRNA codons, involving small ribosomal subunit conformational closure enabling EF-Tu and GTP hydrolysis, applies to the second and third anticodon positions only, not the first (wobble) position [43]. For most amino acids, the tRNA wobble position was selected to broaden recognition of mRNA codons, supporting code degeneracy and making tRNAs more readily available for insertion of the encoded amino acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identify two features of translation systems that are relevant. First of all, in the decoding center of the ribosome, proofreading of anticodon base pair attachments to mRNA codons, involving small ribosomal subunit conformational closure enabling EF-Tu and GTP hydrolysis, applies to the second and third anticodon positions only, not the first (wobble) position [43]. For most amino acids, the tRNA wobble position was selected to broaden recognition of mRNA codons, supporting code degeneracy and making tRNAs more readily available for insertion of the encoded amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…The initial code evolved to utilize any mRNA sequence to synthesize polyglycine, used to stabilize protocells. According to this view, conformational tightening and EF-Tu and GTP proofreading of Watson-Crick base pairing between the anticodon and the codon in the second and third anticodon positions [43] became necessary at the 8→16 letter stage. The 8 letter stage is characterized by resolution of purines and pyrimidines only, but not individual bases, in the first mRNA codon position and the corresponding third tRNA anticodon position.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior studies have shown that DNA polymerases cannot undergo the necessary conformational changes needed for catalysis when dG•dT is in a wobble conformation 7 and all available structures of catalytically active polymerases with bound mismatches within the active site feature WC-like dG•dT or dA•dC geometries 6,7 . Similarly, WC-like rG•rU mismatches have been shown to form in the first and second codon positions of catalytically active ribosomes 9 , in which wobbles are typically rejected 5 , potentially helping to explain translational error hotspots 41 .…”
Section: Tautomerization/ionization During Misincorporationmentioning
confidence: 99%
“…1b) and potentially give rise to spontaneous mutations. Decades later, it is well established that the replicative and translational machineries form a tight grip around the WC geometry to discriminate against mismatches 25 . There is also evidence that both tautomeric 613 (Fig.…”
mentioning
confidence: 99%
“…As the first recorded nucleoside modification within the sequence of an anticodon, 2 Crick introduced inosine in his 1966 Wobble Hypothesis. 1 While the first two bases of the codon undergo traditional base-pairing without exception, 96 Crick proposed the potential for non-canonical base pairs between the first base of the anticodon (“wobble” position 34) and the third base of the codon, U 34 ○G3, or I 34 ○A3/U3/C3 (Fig. 5).…”
Section: The Wobble Hypothesis and The Modulation Of Inosine Wobblingmentioning
confidence: 99%